2000
DOI: 10.1002/1097-0010(200008)80:10<1510::aid-jsfa673>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Beef broth flavour: study of flavour development

Abstract: Of the range of preparation conditions studied here, the beef broths with the most favourable sensory characteristics (P 0.05) were those manufactured with minced meat in a 7.5 g l À1 NaCl solution in proportions of 1:2 (w/v), heated at 85°C for 60 min (the beef broth¯avour was clean, clear, without any off-¯avour). Our data indicate the importance of accurately determining the heat treatment, since intermediate treatments yielded beef broths of good quality, whereas less intense treatments produced broths wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The relationship between beef stock components and the flavor developed at different cooking temperatures has been further studied by Cambero et al( 174 ) The combined sensory study (descriptive analysis and rank order test with 9 trained panelists) with chemical analyses showed a significant increase of small non-amino acid nitrogen compounds, creatine, GMP, IMP, and AMP with beef stock flavor intensity. The beef stock obtained at 85 °C was found by sensory analysis to have the most acceptable flavor, presumably related to the free sugars and amino acids and their reaction products.…”
Section: Food Processing (Cookery)mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between beef stock components and the flavor developed at different cooking temperatures has been further studied by Cambero et al( 174 ) The combined sensory study (descriptive analysis and rank order test with 9 trained panelists) with chemical analyses showed a significant increase of small non-amino acid nitrogen compounds, creatine, GMP, IMP, and AMP with beef stock flavor intensity. The beef stock obtained at 85 °C was found by sensory analysis to have the most acceptable flavor, presumably related to the free sugars and amino acids and their reaction products.…”
Section: Food Processing (Cookery)mentioning
confidence: 99%
“…Furthermore, Cambero et al( 175 ) investigated the flavor development of beef stock in more detail by studying the effect of the cooking temperature, cooking time, ratio of meat and water, and NaCl concentration. They found that the cooking temperature is important since less intense heat treatments generated raw meat, bloody, and metallic flavors whereas stocks prepared at higher temperatures generated sour, astringent, and warmed-over flavors (WOF).…”
Section: Food Processing (Cookery)mentioning
confidence: 99%
“…This reaction takes place easily under heating conditions (Pais et al 1999). The addition of creatine to broths has also been strongly recommended because of its contribution to the full flavour of meat extracts (Schlichtherle-Cerny and Grosch 1998; Cambero et al 2000). However, the presence of creatine and creatinine in cooked meat has also been associated to negative aspects because creatine and creatinine can constitute important precursors of heterocyclic amines formed on the surface of meat when it is cooked at high temperatures such as roasting, frying and grilling (Pais et al 1999).…”
Section: Creatine and Creatininementioning
confidence: 99%